The Daily Financial Management Impact on Building Autonomous Character among Islamic Boarding School Students - Randa Ramadhan; Ekrita Yanova; Liza Efriyanti (at-Tahsin, 2026)
This study investigates the impact of daily financing practices on the development of independence among student in Islamic boarding schools. The research problem addresses how financial management routines, such as budgeting, saving, and managing personal expenses, contribute to the formation of independence in new student, who are exposed to these practices as part of their daily lives at the boarding school. Using a case study design with a qualitative approach, this research involved in-depth interviews and observations, chosen purposively to represent the diversity of experiences. The data analysis was conducted through thematic coding, identifying key patterns in the financial habits of student and how these practices influence their independence. Findings reveal that daily financing routines are closely linked to the development of self-reliance, with sense of responsibility in managing personal finances. Furthermore, the ability to make financial decisions independently strengthens their overall confidence in other aspects of life. Financial discipline not only supports the practical aspects of daily living but also fosters a deeper understanding of budgeting, prioritizing needs, and avoiding impulsive behaviour. A significant portion of the student expressed that these financial habits significantly contributed to their personal growth and independence. Based on these findings, it is recommended that future studies examine the long-term effects of financial education within Islamic boarding school and its broader impact on character development.